Analysis Of Character Formation Through Values In Schools - Reysani (Yayasan Al-Afif, 2024)
The aim of writing this article is to analyze character formation through religious values in schools. The method used is a literature study that emphasizes the study of literature according to the main topics. The analysis results show that character formation through religious values in schools can make students become children with good morals, good personalities, helpful attitudes, honesty, politeness, and respect for others, and always practice the teachings of Islam. Religious values can reflect the growth and development of religious life consisting of three main elements: belief, worship, and morals. The application of religious character formation in schools can be implemented through classroom and extracurricular learning, using various methods such as habituation, advice, exemplary, and punishment methods.